The lost treasure of the polychrome wooden (`ajami) interior of Ghazalyeh House, Aleppo, Syria - Alafandi, Rami; Abdul Rahim, Asiah (Elsevier B.V, 2016)
The objective of this paper is to show the significance of decorated rooms in the Ghazalyeh House in Aleppo, Syria. Polychrome wooden (`ajami) decorations became particularly popular throughout the Near East in the 17th century. Today, impressive polychrome wood (`ajami) interiors dating from the 17th to the 19th century are preserved in Aleppo. Ghazalyeh House was built in 1691 by Khajadour Bin Murad Bali. Later Saba 'Aidaa lived in this house followed by the Ghazaleh family with more than 45 people living in it. The early 20th century the house was converted into a school. By 2007, the Aleppo Antiquities and Museums Directorate refurbished the Ghazaleh House and transformed it into a historical museum for the City of Aleppo. In conjunction with this endeavor, they restored its polychrome wooden panels from 2009-2011. However, in 2013 the polychrome wooden panels were stolen during the war in old Aleppo city. Aleppo is the second largest city in Syria (after the capital Damascus) and it is the commercial capital of Syria. Aleppo has a long history, extending from the third millennium B.C to the Islamic era. Many pieces of literature mentioned that the Amorites were the first inhabitants of Aleppo during the third millennium BC. In 223 BC, the Greek commander (Seleucus Nikator) re-organized and planned the city. Later, Islamic rulers made Aleppo a great by re-building its walls, gates, towers and citadel. The Muslims also built mosques, schools, houses, inns, markets, hospitals, bathrooms, and public facilities. Consequently, Aleppo flourished and became a very important station on the Silk Road; the third largest city in the Ottoman Empire after Istanbul and Cairo. Aleppo was part of the Ottoman Empire from 1516 to 1918. As part of this empire, local Aleppine craftsmen combined their techniques and cultural heritage with Ottoman architecture and design. Due to growth in population the Ottomans expanded the city, provided facilities and established neighborhoods outside of the walls. These neighborhoods outside the walls were mostly for rich people and contained the biggest treasure of polychrome wood (`ajami) in Aleppo, which has become the icon of Ottoman Syrian art. Polychrome wood includes several geometric, floral motifs, and inscriptions. These motifs have rich symbolic backgrounds, originating from house owners, artists, their native culture and religion. This research employs a historical and descriptive approach to explore the thoughts and principles exemplified in the polychrome wooden (`ajami) motifs, and to analyze the connection between different types of Islamic art and polychrome wooden motifs. This paper will highlight some recommendations to protect and restore the traditional houses in Aleppo.